Predicting sandy soil moisture content with hyperspectral imaging - Haijun, Qi; Xiu, Jin; Liu, Zhao; Maxime, DEDO Irene; Shaowen, Li (International Journal of Agricultural and Biological Engineering, 2017)
In this study, a rapid and non-invasive technology for predicting soil moisture content (SMC) was presented based on hyperspectral imaging (HSI). Firstly, a set of HSI system was developed to collect both spectral (400-1000 nm) and spatial (1620×841 pixels) information from sandy soil samples with variable SMC levels in the laboratory. Principal component analysis (PCA) transformation, K-means clustering, and several other image processing methods were performed to obtain a region of interest (ROI) of soil sample from the original HSI data. Then, 256 optimal spectral wavelengths were selected from the average reflectance of the ROI, and 28 textural features were extracted using a gray-level co-occurrence matrix (GLCM). Data dimensionality reduction was conducted on both the spectral information and textural information by using a partial least square algorithm. Six latent variables (LVs) extracted from the spectral information, four LVs extracted from the textural information and fused data were used to build regression models with a three-layer BPNN, respectively. The results showed that all of the three calibration models achieved high prediction accuracy, particularly when using spectral information with R2C=0.9532 and RMSEC=0.0086. However, validation models demonstrate that predicting SMC using fused data is more effective than using spectral reflectance and textural features separately, with a R2P=0.9350 and RMSEP=0.0141, thus proving that the HSI technique is capable of detecting SMC.Keywords: hyperspectral imaging, soil moisture content, image processing, prediction model, fused data, BPNN, regressionDOI: 10.25165/j.ijabe.20171006.2614Citation: Qi H J, Jin X, Zhao L, DEDO I M, Li S W. Predicting sandy soil moisture content with hyperspectral imaging. Int J Agric & Biol Eng, 2017; 10(6): 175–183.